Assessment of Counselling Interventions for Enhancing Effective Participation of Young Adults in Adult Literacy Programmes - Ajayi, Rachael Adejoke (European Scientific Journal, ESJ, 2026)
Low engagement of young adults in adult literacy initiatives continues to hinder efforts to improve foundational skills and promote sustainable human development in Nigeria. Despite the presence of literacy centres across communities, many young adults exhibit irregular attendance, low involvement, and high dropout rates, largely due to socio-economic constraints, psychological challenges, and limited structured learner support. This study examined how motivational, psychosocial, and career-focused counselling interventions influence the participation of young adults in adult literacy programmes within the Amuwo-Odofin Local Government Area. A descriptive survey research design was adopted, and a structured questionnaire was administered to 300 young adults, with 285 completing it satisfactorily. The instrument demonstrated strong internal reliability, with Cronbach’s alpha values ranging from 0.78 to 0.86. Data analysis involved descriptive statistics, Pearson Product-Moment Correlation, and multiple regression analysis. Findings revealed high levels of counselling support associated with increased learner participation. Motivational counselling showed the strongest positive correlation with participation (r = 0.62, p < 0.01), followed by psychosocial counselling (r = 0.58, p < 0.01) and career counselling (r = 0.55, p < 0.01). Multiple regression results indicated that the three counselling components jointly explained 53% of the variance in participation (R = 0.73, R² = 0.53, p < 0.001). Each counselling dimension made significant independent contributions, indicating that counselling interventions enhance attendance, engagement, and retention among young adult learners. The study concludes that counselling interventions are vital for strengthening participation in adult literacy programmes. It recommends the integration of structured counselling services, training of facilitators in counselling skills, and the provision of psychosocial and career support to address learners’ holistic needs and improve programme outcomes.